Accounting for the Costs of Pension Plans (Book). - Zeff, Stephen A.; Ganner, T. A. (The Accounting Review, 1964)
Reviews the book "Accounting for the Costs of Pension Plans: A Research Study," by W.B. Coutts and R.B. Dale-Harris.